Design, Implementation and Test of a Novel Cylindrical Permanent Magnet DC Linear Motor - Demirkol, Ziya; Hasirci, Ugur; Demirci, Recep (MDPI AG, 2023)
Electric motors that convert electrical energy into motion are one of the basic components of automation systems. In these systems, either linear or circular motion is needed. Linear motion can be obtained either from motors that generate circular motion with the help of ancillary equipment or directly by the means of a linear motor. Obtaining linear motion from motors that produce rotary motion leads to additional costs and reduced efficiency. Linear motors, on the other hand, eliminate the need for conversion mechanisms. Despite this advantage, linear motors have some disadvantages, such as length limitation and low force/current ratio. In this study, a novel Cylindrical Direct Current Linear Motor (CDCLM) with high force/current ratio and no length limitation (long stroke) has been developed. Analyses of the developed motor has been performed with an analytical method. In addition, detailed numerical analyses have been carried out in an Ansys-Maxwell environment. A prototype of the designed DC linear motor has been implemented in a laboratory environment and experimental analyses have been carried out. The results of analytical, numerical and experimental analyses have been compared.
Keywords: Technology; linear motor; T; cylindrical motor; permanent magnets; Ansys-Maxwell; Ansys-Maxwell; cylindrical motor; linear motor; permanent magnets; 7. Clean energy